The Analysis of Implementation Business Model Canvas At The E-Marketplace Dipeta Company - Purnawati, Ni Wayan; Setyohadi, Djoko Budiyanto (Scientific Journal of Informatics, 2017)
In the internet Era as now everything is easily accessible, obtaining good information, education, services even trade. E-Marketplace as a new innovation for interaction between buyer and seller can also encourage micro medium to promote his business. www.pesansaja.com released by dipeta in the field of E-Marketplace of local culinary, which still require a lot of innovation to be able to attract customers and keep them. Innovation is also needed to be able to compete with other competitors on the E-Marketplace that engaged in the same. Hence the need for the implementation of the business model in this business model Canvas to get new business models to suit the wishes of the customer and an evaluation based on the strong and weak points of this business. The results of the implementation are expected to make the company's E-Marketplace is getting big and compete at a national level as an E-Marketplace of successful culinary attract customers